Predictors for the need of surgery in antenatally detected hydronephrosis due to UPJ obstruction – A prospective multivariate analysis. Issue 5 (October 2015) - Arora, S.; Yadav, P.; Kumar, M.; Singh, S. Kumar; Sureka, S.Kumar; Mittal, V.; Ansari, M.S.
Summary: Introduction: Disagreement exists over the ability of different diagnostic tests to define obstruction, indications and timing of surgery and which patients will benefit from surgical intervention in antenatal hydronephrosis (ANH) due to ureteropelvic junction obstruction (UPJO). We try to find a way to predict which patients of ANH due to UPJO will eventually need surgery during conservative management. Material and methods: Prospective single centre study involving 122 renal units at a referral centre in India. Patients on conservative management were followed using a standard protocol and operated for pre-defined indications defining failure of conservative management. Patients who underwent surgery were compared with the non-operated group in terms of sex, side, baseline grade of hydronephrosis, maximum anterioposterior diameter on first postnatal ultrasound and differential renal function on first renal scan. Results: A total of 109 renal units qualified for conservative management. Of those, 23.9% required operative intervention during follow-up. Median time to failure of conservative management was 37 weeks. The median follow-up of non-operated cases was 54 months. Univariate analysis revealed that society of fetal urology (SFU) grade of hydronephrosis, anteroposterior diameter (APD), cortical thickness (CT), and pre-operative differential renal function (DRF) had a significant association with surgery (P < 0.05). Multivariate analysis revealed APD and pre-operative DRF as the only independent predictors for requiring surgery, while CT and initial SFU grade of hydronephrosis were not. Receiver operating curve analysis showed that an APD of 24.3 mm could predict the need for surgery, with a sensitivity of 73.1% and a specificity of 88.0%. Conclusions: APD and DRF are the predictive factors for surgery. We stop short of recommending surgery only on the basis of APD. Instead we recommend that efforts be made to improve the specificity of this criterion, or by using APD in perspective with the differential renal function. We can reduce the burden of investigations in those with APD <24 mm while those with APD >24 mm can be more comprehensively monitored.